A Studio Based Approach to Enhancing Decision Making in Sme Start-Up - Ejiri, Annabella Habinka; Nabukenya, Josephine; Sol, Henk G. (In 7th International Conference On Computing and ICT Research, 2011)
The start-up phase plays an important role in the success and survival of many enterprises, which greatly depends on adequate and timely services for decision making. However, deciding to startup a mining Small and Medium Enterprise (SME) is a challenging task for many entrepreneurs in Uganda. Research on SME start-up support is limitedly available. Information Communication and Technology (ICT) is envisaged to facilitate enterprise start-ups. However, there are still acknowledged defi ciencies in Uganda due to their discrete and isolated approach of technology, stakeholders and processes. There is lack of a generalized and systematic means to carrying out SME start-up that emphasizes constant communication and prioritization to support decision processes. Hence, this design science research aims to enhance ill-structured mining SME start-up decision processes with a decision enhancement studio. This studio consists of services for participants in an interactive environment to enhance the enterprise start-up decision processes by doing an analysis of the decision alternatives. This paper presents a design of the decision enhancement studio for mining SME start-ups. The studio is based on the requirements derived from literature and an exploratory study in Uganda. The future research will be dedicated to the implementation, evaluation, and refi nement of the decision enhancement studio for mining enterprise start-ups.
Keywords: Small and Medium Enterprise, Start-up, Decision Enhancement, Studio